AN OVERVIEW OF HIV POSITIVE PATIENTS IN MIMIKA REGENCY PAPUA ON 2019 - Rosa YA Faot; July Ivone; Limdawati Kwee (Universitas Kristen Maranatha, 2024)
Human Immunodeficiency Virus (HIV) is an infection that attacks and damages our body's immune system, resulting in immune deficiency. According to UNAIDS report, in 2018 approximately around 640,000 people in Indonesia live with HIV, of whom there were 46,000 people newly infected by HIV and 38,000 died because of AIDS. This research aims to determine the characteristic of HIV patient in Mimika, Papua in 2019 according to age, sex, marital status, pregnancy status, education, occupation, risk category, visitation status, spouse's HIV status, mode of transmission, and comorbid. This is a descriptive observational and retrospective studies using medical records of HIV patient with whole sampling method. The result showed that the prevalence of HIV patient was 345 cases with 337 among them fulfilled the criteria. As conclusion, highest incidence acquired at age 25-49 (69.7%), the most sex was women (50.4%), most marital status was married (57%), most pregnancy status was not pregnant (84.7%), latest education was senior high school (45.7%) most occupation was private employee (24.9%) the most risky group was high risk couple (65%), most visit status was unaccompanied (98.8%), most spouse's HIV status was unknown (91.4%), most mode of transmission was sexually (97.3%), and the most patient's comorbid was none (26.1%).